2021
DOI: 10.1080/22221751.2021.1899057
|View full text |Cite
|
Sign up to set email alerts
|

Viral evolution sustains a dengue outbreak of enhanced severity

Abstract: Compared to the previous 2013–2014 outbreak, dengue 2016–2017 outbreak in New Caledonia was characterized by an increased number of severe forms associated with hepatic presentations. In this study, we assessed the virological factors associated with this enhanced severity. Whole-genome sequences were retrieved from dengue virus (DENV)-1 strains collected in 2013–2014 and from severe and non-severe patients in 2016–2017. Fitness, hepatic tropism and cytopathogenicity of DENV 2016–2017 strains were compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…However, the variability of cocirculating flaviviruses is typically determined by comparing the genome sequence instead of the phenotype. It has been suggested that some strains of DENV and ZIKV could be associated with enhanced severity of outbreaks or epidemiological replacements, but the characterization of phenotypes that could explain these differences in transmissibility or virulence between Flavivirus variants is rarely explored ( Zhang et al., 2005 ; De Castro et al., 2013 ; Xia et al., 2018 ; Aubry et al., 2021 ; Inizan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the variability of cocirculating flaviviruses is typically determined by comparing the genome sequence instead of the phenotype. It has been suggested that some strains of DENV and ZIKV could be associated with enhanced severity of outbreaks or epidemiological replacements, but the characterization of phenotypes that could explain these differences in transmissibility or virulence between Flavivirus variants is rarely explored ( Zhang et al., 2005 ; De Castro et al., 2013 ; Xia et al., 2018 ; Aubry et al., 2021 ; Inizan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the pooled prevalence estimate for severe forms of dengue (DHF, DSS or severe dengue) was 1.92% in the general population, with DHF estimated at 2.34% (95% CI 0.61–5.04) and severe dengue estimated at 1.10% (95% CI 0.39–2.14). The prevalence of these severe forms increased to 23.23% (95% CI 13.58–34.53) in hospitalised cohorts, with DHF prevalence estimated at 21.06% (95% CI 7.48–39.07), DSS estimated at 4.11% (95% CI 0.02–13.39) and one study reporting severe dengue in 24.64% of patients 51 . In both patient cohorts, no publication bias was detected and excluding one study at a time during sensitivity analysis did not alter effect size significantly apart from one study in the general population cohort 52 and another study in the cohort of hospitalised patients, 53 both of which reported significantly higher rates of DHF (see supplementary materials and for further details).…”
Section: Resultsmentioning
confidence: 99%
“…5,7 The incidence and clinical manifestations of dengue-associated liver injury vary widely between studies, probably due to discrepancies in case definition, differences in viral strains, host susceptibilities and comorbidities including preexisting liver disease. 10 As an upsurge of dengue-associated hepatic presentations occurred recently in several territories, 11 it appears crucial to systematically review dengue-associated liver involvement.…”
Section: Introductionmentioning
confidence: 99%